2019
DOI: 10.3727/105221618x15361728786767
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Gene Expression Analysis Identifies Chronic Alcohol-Mediated Shift in Hepatocyte Molecular States After Partial Hepatectomy

Abstract: The analysis of molecular states of individual cells, as defined by their mRNA expression profiles and protein composition, has gained widespread interest in studying biological phenomena ranging from embryonic development to homeostatic tissue function and genesis and evolution of cancers. Although the molecular content of individual cells in a tissue can vary widely, their molecular states tend to be constrained within a transcriptional landscape partly described by the canonical archetypes of a population o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Lately, single-cell transcriptomic methods are being employed to probe cellular heterogeneities of tissues and reconstruct developmental trajectories of individual organs (Haghverdi et al, 2016;Saelens et al, 2019;Schiebinger et al, 2019). In the case of the liver, this has led to the identification of previously unknown subpopulations of hepatocytes, cholangiocytes, endothelial cells, scar-associated macrophages, stellate cells, and myofibroblasts from healthy and diseased conditions (Aizarani et al, 2019;Dobie et al, 2019;Hyun et al, 2019;MacParland et al, 2018;Pepe-Mooney et al, 2019;Ramachandran et al, 2019;Xiong et al, 2019;Achanta et al, 2019;Cook et al, 2018). The studies revealed that more than 50% of hepatocyte genes follow a discrete zonated expression pattern in a liver lobule, and surprisingly, similar metabolic zonation exists for LSECs and stellate cells Halpern et al, 2018;2017).…”
Section: Discussionmentioning
confidence: 99%
“…Lately, single-cell transcriptomic methods are being employed to probe cellular heterogeneities of tissues and reconstruct developmental trajectories of individual organs (Haghverdi et al, 2016;Saelens et al, 2019;Schiebinger et al, 2019). In the case of the liver, this has led to the identification of previously unknown subpopulations of hepatocytes, cholangiocytes, endothelial cells, scar-associated macrophages, stellate cells, and myofibroblasts from healthy and diseased conditions (Aizarani et al, 2019;Dobie et al, 2019;Hyun et al, 2019;MacParland et al, 2018;Pepe-Mooney et al, 2019;Ramachandran et al, 2019;Xiong et al, 2019;Achanta et al, 2019;Cook et al, 2018). The studies revealed that more than 50% of hepatocyte genes follow a discrete zonated expression pattern in a liver lobule, and surprisingly, similar metabolic zonation exists for LSECs and stellate cells Halpern et al, 2018;2017).…”
Section: Discussionmentioning
confidence: 99%
“…is inactivated in some individuals with alcohol-induced liver injury, causing extensive repopulation of SAH livers with immature, fetal-like cells. The results identify the mechanism for liver failure in SAH by revealing that TNF-α and IL-1β ( 19), proinflamma-prevented maturation of hepatocytes (8), which explains why liver regeneration is inhibited by alcohol (17,18). However, the mechanisms involved were not defined.…”
Section: Introductionmentioning
confidence: 98%
“…Single-cell gene expression analysis recently demonstrated that feeding alcohol to adult rats increased the proportion of hepatocytes that are either becoming proliferative or proliferat-ing (8), suggesting that excessive alcohol drinking might promote some degree of hepatocyte dedifferentiation. Maintaining hepatocytes in a differentiated state is a critical function of the Hippo/ YAP signaling pathway (9).…”
Section: Introductionmentioning
confidence: 99%
“…This protocol has been developed over the past decade in our lab to enable reliable high-throughput detection of gene expression by qRT-PCR in low input samples starting from 10 pg total RNA (single cells). We have used this protocol to measure gene expression in a wide variety of samples types, tissue treatments and disease contexts (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The present version of this protocol was developed as part of the National Institutes of Health SPARC project efforts to construct a comprehensive anatomical, molecular and functional map of the peripheral nervous system at the visceral organs.…”
Section: Introductionmentioning
confidence: 99%